Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Doped NiFe2O4 spinel oxygen carriers for enhanced H2 production in photo-assisted chemical looping reforming with water splitting under mild conditions - Yunkun Zhao; Shuting Min; Yibo Guo; Guangxuan Chen; Rongjing Wang; Xiaolong Xu; Jing Huang; Yang Hu; Tingting Xu; Xun Wang (Journal of Cleaner Production, 2026)

Study on the Effects and Mechanisms of Resveratrol in Improving Cognitive Impairment in Aβ1−42-Induced Alzheimer’s Disease Model Mice - Chu Zhang; Yunhan Ma; Zhidan Shi; Xinqi He; Jiayi Hu; Shuting Chen; Hao Wu; Meng Tian; Chuang Yan; Mengtao Xing; Ling He (Journal of Neuroimmune Pharmacology, 2026)

Correction: Eradication Efficacy of Antimicrobial Peptide CRAMP-34 Against Mixed-Species Biofilms Formed by Staphylococcus aureus and Pseudomonas aeruginosa - Huiming Hu; Miao You; Tengyue He; Lihong Yuan; Fan Wang; Yanshuang Huang; Huizhen Zhu; Ruiqi Chen; Shuting Liu; Wei Wei; Hongzao Yang; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2026)

Fabrication of monovalent cation perm-selective membranes via quaternized poly(aryl ether sulfone) modification for efficient Li+/Mg2+ separation - Shuting Zhang; Yunxiang Ouyang; Khalznkhuu Otgonlkhagva; Jiaze Li; Jialin Lv; Na Li; Zhaoxia Hu; Shouwen Chen (Desalination, 2026)

Eradication Efficacy of Antimicrobial Peptide CRAMP-34 Against Mixed-Species Biofilms Formed by Staphylococcus aureus and Pseudomonas aeruginosa - Huiming Hu; Miao You; Tengyue He; Lihong Yuan; Fan Wang; Yanshuang Huang; Huizhen Zhu; Ruiqi Chen; Shuting Liu; Wei Wei; Hongzao Yang; Hongwei Chen (International Journal of Peptide Research and Therapeutics, 2026)

Long-term assessment of natural mineral-based electrochemical systems for concurrent wastewater treatment and nutrient recovery - Yukun Xing; Shuting Chen; Baile Wu; Xiyuan Feng; Ke Hu; Xiaoxiang Zhang; Junyu Zhou; Jingsheng Shi; Yafei He; Peng Li; Zhengyu Jin (Journal of Water Process Engineering, 2026)

Effects of sulfamethoxazole stress on pollutant removal performance of unsaturated constructed wetlands - Yuechang Wang; Linlan Zhuang; Yuanjun Su; Shuang Liu; Zhen Hu; Jian Zhang; Xiaoping Wang; Shaoming Cui; Gang Peng; Shuting Xie (Journal of Environmental Sciences, 2026)

Nanoengineering of STING-IDO1 feedback machinery potentiates antitumor immunity - Yanming Xia; Lixin Hu; Xiaohu Wang; Mingxi Li; Bo Shi; Siqi Zhu; Yutong Wu; Shuting Xiang; Lifang Yin; Suxin Li (Chemical Engineering Journal, 2026)

An extra-large panicle gene ELP1 from wild rice Oryza officinalis increases grain number and grain yield - Jiachen Ma; Mei Li; Yanan Lin; Jinjin Lian; Yizhengnan Zhu; Jing Yang; Wenfan Hu; Luyi Zhang; Shuting Li; Weilin Zhang (Theoretical and Applied Genetics, 2026)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

New insights into the impact of heavy metals on phosphorus recovery: Interaction with the phase transition of CaP precipitation - Xiang Li; Xin Hu; Shuting Shen; Rui Wan; Guo Ting; Xiwu Lu (Journal of Environmental Chemical Engineering, 2025)

Synergistic impact of starch-tannic acid complex in regulating gut microbiota to produce propionate - Shuting Duan; Yiming Hu; Xiaowei Zhang; Enpeng Li; Cheng Li (Carbohydrate Polymers, 2025)

Characterization of microRNAs, phasiRNAs and hc-siRNAs in Citrus sinensis during Candidatus Liberibacter asiaticus infection - Yanan Hu; Nannan Lu; Shuting Liu; Kaiqiang Bao; Ruimin Li; Guiyan Huang (Horticulture, Environment, and Biotechnology, 2025)

Cognitive experiments on labelling uncertainty for LCZ mapping across heterogeneous megacities in China: Introducing multi-source geospatial data and LCZ subclasses - Xilin Zhou; Jinyang Hu; Shuting Yan; Chuancheng Li (Urban Climate, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

Greenery strategies for reducing pedestrian particulate exposure along an open-flanked urban arterial road - Zhanyong Wang; Yanying Rao; Xinyuan Lin; Shuting Chen; Xisheng Hu (Urban Climate, 2025)

Thermal management of photovoltaic systems using cascade phase change material module - Tingting Wu; Lianjian Mo; Guiyang Ye; Yanxin Hu; Changxiang Fan; Mingjiang Zeng; Shuting Cai; Mengjie Song (Building and Environment, 2025)

Buprofezin causes early developmental toxicity of zebrafish (Danio rerio) embryos: morphological, physiological and biochemical responses - Shuting Qiang; Yufeng Che; Mingyang Lu; Yuan Tian; Lin Gao; Jingwen Chen; Tingzhang Hu (Aquatic Toxicology, 2025)

Targeting 5-HT to Alleviate Dose-Limiting Neurotoxicity in Nab-Paclitaxel-Based Chemotherapy - Shuangyue Pan; Yu Cai; Ronghui Liu; Shuting Jiang; Hongyang Zhao; Jiahong Jiang; Zhen Lin; Qian Liu; Hongrui Lu; Shuhui Liang; Weijiao Fan; Xiaochen Chen; et al. (Neuroscience Bulletin, 2025)

Antioxidant and antimicrobial sodium alginate/sodium carboxymethyl cellulose films loaded with self-assembled hesperidin nanorods for fruits preservation - Zexin Gao; Shuting Xie; Li Chang; Huijuan Tang; Zhimin Sun; Yong Deng; Yinqi Hu; Ying Xu; Mingbao Luan (Food Chemistry, 2025)

Solid membrane-based aqueous lithium extraction and adsorption: Advances, challenges, and prospects - Yueru Yang; Shumin Bi; Faquan Wang; Xinyu Pan; Tianci Yang; Shui Hu; Shuting Tang; Qingxiu Jia (Chemical Engineering Journal, 2025)

ITIMCA: Image-text information and cross-attention for multi-modal cassava leaf disease classification based on a novel multi-modal dataset in natural environments - Huinian Li; Baoyu Chen; Jingjia Chen; Shuting Li; Feiyong He; Yingbiao Hu (Crop Protection, 2025)

Spatial and seasonal distribution, sources, and health risks of PM2.5 loaded per- and polyfluoroalkyl substances (PFASs) in a typical megacity - Shuting Li; Guanjiu Hu; Beibei Zhang; Xuewen Yao; Zhihuai Chen; Xiaosan Luo (Science of The Total Environment, 2025)

KOH-modified biochar enhances nitrogen metabolism of the chloroquine phosphate-disturbed anammox: Physical binding, EPS modulation and versatile metabolic hierarchy - Rui Hu; Xue Chen; Yule Han; Wanjiang Li; Shuting Zhang; Zhaobin Liu; Jiandong Wang; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2025)

Unravelling key factors controlling homogeneous crystallization during phosphorus recovery: From the perspective of crystallization kinetics - Xiang Li; Xin Hu; Shuting Shen; Rui Wan; Hongliang Dai; Xiwu Lu (Journal of Cleaner Production, 2025)

Tissue distribution of emerging per- and polyfluoroalkyl substances in wild fish species from Qiantang river, east China: Comparison of 6:2 Cl-PFESA with PFOS - Kejun Hu; Zhuoren Shen; Shuting Wang; Liqun Zhang (Environmental Research, 2024)

The impact of anthropogenic pressures on microbial diversity and river multifunctionality relationships on a global scale - Qian Qu; Shuting Wang; Xiangang Hu; Li Mu (Science of The Total Environment, 2024)

Natural enzyme cascade bimetallic sulfide MoCuSx nanozyme for synergistic photothermal/photodynamic enhanced chemodynamic antimicrobial therapy of wound infection - Caiyun Xu; Junqin Li; Chunlei Ou; Jing Yang; Shuting Fu; Weiqing Hu; Li Wang; Zefeng Wang; Luo Hai; Le Deng; Dinggeng He (Chemical Engineering Journal, 2024)

Integrated transcriptome and SNP analysis reveals sex-related genetic insights in the black-spotted frog (Pelophylax nigromaculatus) - Xingyue Zhang; Gang Wan; Ziwei Li; Qiufu Wu; Shuting Xiong; Xiaoqing Wang; Lilang You; Yazhou Hu (Aquaculture International, 2024)

4-tert-Butylphenol impairs the liver by inducing excess liver lipid accumulation via disrupting the lipid metabolism pathway in zebrafish - Huiyun Wang; Juan Liu; Shuting Qiang; Yufeng Che; Tingzhang Hu (Environmental Pollution, 2024)

Antimicrobial effect of plasma-activated water combined with tartaric acid against Staphylococcus aureus and its application on fresh-cut asparagus lettuce - Wei Wu; Jing Zhang; Tangjun Li; Zhenyang Hu; Shuting Huang; Mengshi Lin; Yunfei Xie; Zhilong Yu (Food Bioscience, 2024)

Suppressing the Jahn–Teller effect in Mn-based Prussian blue analogues by linear (N O) anions - Qinghao Han; Zonghua Yang; Ya’nan Hu; Shuting Gao; Xingjun Liu; Cuiping Wang; Jiajia Han (Chemical Engineering Journal, 2024)

Natural organic small molecules promote the aging of plastic wastes and refractory carbon decomposition in water - Xiangang Hu; Shuting Wang; Ruihong Feng; Kai Hu (Journal of Hazardous Materials, 2024)

Measuring and modeling the effects of green barriers on the spatial distribution of fine particulate matter at roadside - Xin Chen; Jie Wu; Wenbin Yang; Zhanyong Wang; Shuting Chen; Xisheng Hu; Kaifa Lu; Zhongmou Fan; Mei Lin; Pu Chen (Urban Climate, 2023)

Vanadium dissolution restraint and conductive assistant in MnV12O31·10H2O to boost energy storage property for aqueous zinc-ion batteries - Shuting Wang; Li Xiong; Guanghui Yuan; Tao Hu; Ulla Lassi; Beibei Wang; Jintao Bai; Gang Wang; Xiujuan Wang (Chemical Engineering Journal, 2023)

Highly active complexes of pyrite and organic matter regulate arsenic fate - Shuting Wang; Jingyu Wen; Li Mu; Xiangang Hu; Ruihong Feng; Yuying Jia (Journal of Hazardous Materials, 2023)

Weibull distribution models for describing soil hydraulic properties over the entire matric suction range - Zhenlei Yang; Zi Li; Xin Tong; Shengjie Hu; Jun Wang; Shuting Ji; Ling Li (Journal of Hydrology, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

Associations of urinary and blood cadmium concentrations with all-cause mortality in US adults with chronic kidney disease: a prospective cohort study - Jia Zhang; Xiao Wang; Zhibin Ma; Ying Dang; Yaya Yang; Shuting Cao; Changping Ouyang; Xiaoru Shi; Jinhua Pan; Xiaobin Hu (Environmental Science and Pollution Research, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

Long-term effect of submicronic particulate matter (PM1) and intermodal particulate matter (PM1-2.5) on incident dyslipidemia in China: A nationwide 5-year cohort study - Meiling Hu; Jing Wei; Yaoyu Hu; Xiuhua Guo; Zhiwei Li; Yuhong Liu; Shuting Li; Yongxi Xue; Yuan Li; Mengmeng Liu; Lei Wang; Xiangtong Liu (Environmental Research, 2023)

Assembling nanocelluloses into fibrous materials and their emerging applications - Bing Wang; Shuting Qiu; Zehong Chen; Yijie Hu; Ge Shi; Hao Zhuo; Huili Zhang; Linxin Zhong (Carbohydrate Polymers, 2023)

Effects of ocean warming and fishing on the coral reef ecosystem: A case study of Xisha Islands, South China Sea - Xinyan Zhang; Yuanchao Li; Jianguo Du; Shuting Qiu; Bin Xie; Weilin Chen; Jianjia Wang; Wenjia Hu; Zhongjie Wu; Bin Chen (Frontiers in Marine Science, 2022)
Global change has generated challenges for oceans, from individuals to the entire ecosystem, and has raised contemporary issues related to ocean conservation and management. Specifically, coral reef ecosystems have been exposed to various environmental and human disturbances. In this study, the Ecopath with Ecosim model was used to explore the impacts of ocean warming and fishing on Xisha Islands coral reef ecosystem in the South China Sea. The variables in this model included two ocean warming scenarios and three fishing scenarios. The model consisted of 23 functional groups including algae, coral, sea birds, and sharks. Our results showed that by the middle of the century, ocean warming and fishing led to a 3.79% and 4.74% decrease in total catch compared with 2009, respectively. In addition, the combined effects of ocean warming and fishing caused a 4.79% decrease in total catch, and the mean trophic level of catch was predicted to decrease by 6.01% under the SSP585-High fishing scenario. Reducing the fishing effort mitigates the effects of ocean warming on some species, such as large carnivorous fish and medium carnivorous fish; however, under low fishing effort, some functional groups, such as small carnivorous and omnivorous fish, have low biomass because of higher predation mortality.

Increased uterine androgen receptor protein abundance results in implantation and mitochondrial defects in pregnant rats with hyperandrogenism and insulin resistance - Yuehui Zhang; Min Hu; Fan Yang; Yizhuo Zhang; Shuting Ma; Dongqi Zhang; Xu Wang; Amanda Nancy Sferruzzi-Perri; Xiaoke Wu; Mats Brännström; Linus R. Shao; Håkan Billig (Journal of Molecular Medicine, 2021)
In this study, we show that during normal rat pregnancy, there is a gestational stage-dependent decrease in androgen receptor (AR) abundance in the gravid uterus and that this is correlated with the differential expression of endometrial receptivity and decidualization genes during early and mid-gestation. In contrast, exposure to 5α-dihydrotestosterone (DHT) and insulin (INS) or DHT alone significantly increased AR protein levels in the uterus in association with the aberrant expression of endometrial receptivity and decidualization genes, as well as disrupted implantation. Next, we assessed the functional relevance of the androgen-AR axis in the uterus for reproductive outcomes by treating normal pregnant rats and pregnant rats exposed to DHT and INS with the anti-androgen flutamide. We found that AR blockage using flutamide largely attenuated the DHT and INS-induced maternal endocrine, metabolic, and fertility impairments in pregnant rats in association with suppressed induction of uterine AR protein abundance and androgen-regulated response protein and normalized expression of several endometrial receptivity and decidualization genes. Further, blockade of AR normalized the expression of the mitochondrial biogenesis marker Nrf1 and the mitochondrial functional proteins Complexes I and II, VDAC, and PHB1. However, flutamide treatment did not rescue the compromised mitochondrial structure resulting from co-exposure to DHT and INS. These results demonstrate that functional AR protein is an important factor for gravid uterine function. Impairments in the uterine androgen-AR axis are accompanied by decreased endometrial receptivity, decidualization, and mitochondrial dysfunction, which might contribute to abnormal implantation in pregnant PCOS patients with compromised pregnancy outcomes and subfertility. Key messages The proper regulation of uterine androgen receptor (AR) contributes to a normal pregnancy process, whereas the aberrant regulation of uterine AR might be linked to polycystic ovary syndrome (PCOS)-induced pregnancy-related complications. In the current study, we found that during normal rat pregnancy there is a stage-dependent decrease in AR abundance in the gravid uterus and that this is correlated with the differential expression of the endometrial receptivity and decidualization genes Spp1 , Prl , Igfbp1 , and Hbegf . Pregnant rats exposed to 5α-dihydrotestosterone (DHT) and insulin (INS) or to DHT alone show elevated uterine AR protein abundance and implantation failure related to the aberrant expression of genes involved in endometrial receptivity and decidualization in early to mid-gestation. Treatment with the anti-androgen flutamide, starting from pre-implantation, effectively prevents DHT + INS-induced defects in endometrial receptivity and decidualization gene expression, restores uterine mitochondrial homeostasis, and increases the pregnancy rate and the numbers of viable fetuses. This study adds to our understanding of the mechanisms underlying poor pregnancy outcomes in PCOS patients and the possible therapeutic use of anti-androgens, including flutamide, after spontaneous conception.

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Histological and Comparative Transcriptome Analyses Provide Insights Into the Immune Response in Pearl Sac Formation of Hyriopsis cumingii - Wenying Shen; Yiwei Hu; Zhengkai He; Shuting Xu; Xinyue Xu; Genfang Zhang; Gang Ren (Frontiers in Marine Science, 2020)